Evaluation of the effect of resin infiltration (Icon) and sodium fluoride varnish on white spot lesions in Erbil City, Kurdistan Region, Iraq - B. hameed, Botan; Alzubaidee, Ali F.; H. Hamonari, Nasreen (Journal of Neonatal Surgery, 2025)
Background: White spot lesions (WSLs) are subsurface enamel demineralizations that appear as white opacities, often posing an aesthetic concern. This study aims to clinically evaluate the effectiveness of resin infiltration compared to fluoride varnish in arresting WSLs, which helps inhibit caries progression and treats them without the need for drilling. Methods: The study included patients aged 8-18 years presenting with at least one WSL with an International Caries Detection and Assessment System (ICDAS) score of 1-2 during active management of multiple bilateral lesions (MBAs). Participants were randomly assigned to receive either resin infiltration (Icon) or fluoride application. Follow-up assessments were conducted after six months, with clinical examinations performed using the ICDAS II system for caries evaluation. The SPSS Statistics software version 28 was used for data analysis. Results: A total of sixty-two patients with an initial diagnosis of white spot lesions participated in the study. No significant differences were observed between groups based on lesion grade, sex, or age. Immediately following treatment, resin infiltration with Icon showed a statistically significant greater improvement in reducing lesion severity compared to sodium fluoride varnish (p < 0.0001). Conclusions: Both resin infiltration and fluoride varnish are practical and effective methods for treating WSLs. The ability of resin infiltration to inhibit caries progression should be considered a viable alternative to fluoride treatments, offering both aesthetic restoration and pore occlusion